Influence of the hydration by the environmental humidity on the metallic speciation and the photocatalytic activity of Cr/MCM-41 - Elías, Verónica Rita (2014)
The influence of the environmental humidity on the Cr species deposited on inorganic supports like MCM-41 silicates was analyzed by UV?vis Diffuse Reflectance (UV?vis RD), Electronic Spin Resonance (ESR) and X-ray near-edge (XANES) spectroscopy. Metal speciation could be inferred, finding that prolonged exposure periods under environmental humidity provoked the reduction of the active Cr6þ species and thus, the decrease of the Cr/MCM-41 photoactivity. After the Ti loading over the Cr modified samples, Cr species and the photoactivity were not notably influenced by the humidity exposure. Thus, it could be concluded that the presence of Ti is important because the TiO2 cover protects the oxidized Cr species, stabilizing them.